Socio-Religious Implications of Sports Betting among Muslim Youths: A Case Study of Tafo Zongo, Ghana - Mustapha Abdullah Kuyateh (CV. Bimbingan Belajar Assyfa, 2025)
Rising unemployment and lax gambling regulations in Africa have fueled the rapid growth of sports betting companies and the increasing participation of youth, including among the Muslim community. This study aims to identify the factors that motivate Muslim youth in Tafo Zongo, Ghana, to engage in sports betting, analyze its impact on their well-being, and formulate coping strategies grounded in Islamic values. The method used was a qualitative approach, with data collected through in-depth interviews with informants, including sports bettors and religious leaders (Imams) in the Tafo Zongo area. The results indicate that the main motivations for participation are economic factors (seeking financial gain), leisure time, and peer pressure. Although soccer gambling is often considered a form of entertainment, findings reveal that its negative impacts far outweigh the short-term benefits, including financial losses that exacerbate poverty and moral degradation that contradict Islamic teachings, which forbid all forms of gambling. In conclusion, this phenomenon requires collaborative intervention between the government through tightened regulations and religious leaders through spiritual education to protect the socio-economic well-being of Muslim youth. This study confirms that without appropriate remedial measures, gambling addiction will continue to undermine the social fabric of Tafo Zongo.